‫دور ‬‫ﻗﻨﻮات‬ ‫اﻟﺘﻮزﻳﻊ‬ ‫ﻓﻲ‬ ‫ﺗﺤﺴﻴﻦ‬ ‫اﻟﻘﺪرة‬ ‫اﻟﺘﻨﺎﻓﺴﻴﺔ‬ ‫ﻟﻠﻤﺆﺳﺴﺔ‬ ‫دراﺳﺔ ‬‫ﺣﺎﻟﺔ‬ ‫ﻣﺆﺳﺴﺔ‬ ‫ﻣﻄﺎﺣﻦ‬ ‫اﻟﻬﻼل‬ ‫–‬ ‫ﺳﻮق‬‫ أﻫﺮاس‬ ‬‬ - ‬‫أﺣﻤﺪ‬ ‫ﺳﺎﻟﻢ ‫ﻣﺤﻤﻮد‬ (My University, 2017)
The research aims to study the role of distribution channels for improve the competitiveness of the company, such as this research interest is based on a range of administrative levels, which are employees from senior management and from the middle and management to the company EL-Hilal mills, and represented the problem of research by trying to study and analyze the extent of the contribution of the channels of distribution to improve the competitiveness of the company, and the pursuit research to achieve a certain number of cognitive and practices based on key assumptions. The questionnaire was used in data and information relating to research collection having been distributed to a sample of 40 staff members of the senior management, middle and executive , perhaps the most important of which was for the data processing used much of the presence of a statistically significant effect of the channels distribution to improve the competitiveness of the mills company EL-Hilal. As part of this study, it was divided into two parts, the first devoted to the theoretical aspects of the study of distribution channels and competitiveness, while the second part in which the parameters Theoretical arguments dropped on the EL-Hilal mills company.